Internalisasi Nilai-Nilai Pendidikan Agama Islam dalam Etika Penggunaan Artificial Intelligence oleh Mahasiswa STAI NW Samawa: Internalization of Islamic Religious Education Values ​​in the Ethics of Using Artificial Intelligence by STAI NW Samawa Students - Muhammmad Parhun; Fahrizal Nur Efendi; Andre Ariyansah; Ashilah Fauziah Syaswina (Pendidikan Al-Gafari, 2026)
The development of Artificial Intelligence (AI) has changed the way students obtain, process, and present academic information. On the other hand, the use of AI also raises ethical challenges, such as academic honesty, scientific responsibility, and the limitations of technology use in completing lecture assignments. This study aims to analyze the process of internalizing Islamic Religious Education values ​​in the ethics of using Artificial Intelligence by STAI NW Samawa students. The study uses a qualitative approach with a case study type. Research informants were selected purposively, namely active students of STAI NW Samawa who utilize Artificial Intelligence in academic activities. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña which includes data condensation, data presentation, and drawing conclusions. Data validity was tested through source triangulation, technical triangulation, and member checking. This study is expected to produce an overview of the process of internalizing Islamic Religious Education values, especially the values ​​of honesty (sidq), trustworthiness (amanah), responsibility (mas'ūliyyah), and academic integrity in the use of AI by students. The research results are expected to contribute to the development of ethics in the use of Artificial Intelligence in Islamic higher education environments and serve as a reference in the preparation of academic policies that are adaptive to technological developments without ignoring Islamic values.